Adolescent-Parent Communication About Reproductive Health Among Junior High School Students - Werdani, Kusuma Estu; Umaroh, Ayu Khoirotul; Snow, Rachel C. (Jurnal Kesehatan Prima, 2024)
Adolescent-parent communication about reproductive health is still considered taboo. This view prevents students from telling their parents about their health problems. This study aimed to analyze the relationship between factors related to adolescent-parent communication about reproductive health. This research method is analytically observational with a cross-sectional approach. Respondents involved were students of classes VII and VIII, totaling 117 people. The results showed no relationship between gender (p-value= 0.182, OR (95%CI)= 0.846-3.686), information access (p-value= 0.561, OR (95%CI)= 0.603-3.314), gender compatibility (p-value= 0.302, OR (95%CI)= 0.707-5.020), and parental credibility (p-value= 0.100, OR (95%CI)= 0.950-4.370) with adolescent-parent communication about reproductive health. Adolescent-parent communication about reproductive health, which is low and high, has almost the same percentage—of recommendations to parents to improve communication with adolescents regarding reproductive health further. The school also needs to add reproductive health education activities.